Bacterial fish pathogens : disease of farmed and wild fish - Austin, B. [ (Brian)] , 1951- (Springer, 2012)
In its completely updated fifth edition, this book explores the biological aspects of the bacteria which cause disease in farmed and wild fish. Covers newly developed applications of molecular approaches to taxonomy, diagnosis and vaccine development